Efficient electrocatalytic reduction and detection of hydrogen peroxide at an IrIVOx·H2O nanostructured electrode prepared by electroflocculation. (1st January 2016) - Liu, Pei-Yin; Sun, Sin-Cih; Chen, Yi-Shiang; Chuang, Min-Chieh
Abstract: An Ir IV Ox·nH2 O nanostructured electrode prepared by electroflocculation is reported; the electrode efficiently catalyzes the electrochemical reduction of hydrogen peroxide (H2 O2 ). Linear sweep voltammograms reveal that the potential onset arising due to the reduction of H2 O2 (1 mM) occurs at -0.1 V (vs. Ag/AgCl), which is more anodic than the onset potential occurring on the glassy carbon electrode by 400 mV, thereby substantiating the catalytic utility of Ir IV Ox·nH2 O. The number of electrons transferred in the process, estimated via the Koutecky-Levich equation, is 1.89 ± 0.30. The Tafel slope obtained from polarization measurements is ca. 240.9 mV/dec. Furthermore, the Ir IV Ox·nH2 O nanostructured electrode exhibits response with linear relationship against H2 O2 concentrations ranging over 0-1 mM (when agitated) and 0-150 μM (in flow injection analysis); the limit of detection (3σ), as determined under flow injection analysis, is 5 μM. The as-fabricated electrode is insensitive to the oxidation of ascorbic acid (0.1 mM) and acetaminophen (0.1 mM) and exhibits stable amperometric response (over twenty successive trials), albeit a slight drift in the sensor response is observed during the initial six evaluations. Based on the results, the electrocatalytic mechanism involving the following steps is proposed: (1) the reduction of Ir from Ir IV to Ir III, (2) catalytic cleavage of the O-O bond to generate OH radicals, and (3) the reduction of the OH radicals to OH − via the reoxidation of Ir III to Ir IV .